Pulmonary Nocardiosis in an Immunocompetent Patient: A Case Report - Reza Ibrahimi; Farid Poursadegh; Mahnaz Mozdourian; Fariba Rezaeetalab; Zohre Emamdadi; Sahar Arab Yousefabadi; Sara Samadi (Clinical Case Reports)
ABSTRACT The patient, a 56‐year‐old female with a history of childhood bronchiectasis and controlled hypertension, presented with fever, cough, and hemoptysis. Despite initial treatment for exacerbation of bronchiectasis, her condition worsened, leading to sepsis. Blood tests revealed leukocytosis and elevated CRP. Lung HRCT showed necrotic consolidation and nodules in the left and right lung, suggestive of necrotizing pneumonia. Bronchoscopy revealed Nocardia species, leading to intravenous co‐trimoxazole treatment. After a week in ICU, the patient improved and was discharged with oral co‐trimoxazole. The patient remained free of relapse during a 6‐month follow‐up period, with no CNS or cutaneous involvement detected.